Addressing the Pandemic's Medium-Term Fallout in Australia and New Zealand. (IMF Working Papers; Working Paper, 2020)
While the world is focused on addressing the near-term ramifications of the COVID-19 shock, we turn attention to another important aspect of the pandemic: its fallout on medium-term potential output through scarring. Taking Australia and New Zealand as examples, we show that the pandemic will likely have a large and persistent impact on potential output, broadly in line with the experience of advanced economies from past recessions. The impact is driven by employment, capital stock, and productivity losses in the wake of an unprecedented sectoral reallocation, hightened uncertainty, and reduced migration. Maintaining fiscal and monetary policy support until the recovery is firmly entrenched and putting in place a strong structural policy agenda to counter the pandemic's adverse effects on medium-term potential output will be important to support standards of living and strengthen economic resilience in case of renewed shocks.